Holistic Approaches in Women’s Reproductive Health Care: Integrating Conventional Medicine and Complementary Therapies - Tepy, Diyah; Afrilia, Eka Mardiana; Faadhilah, Astrisa; Damayanti, Wulan (MSJ : Majority Science Journal, 2025)
This study explores women’s experiences in seeking reproductive health care by examining how they navigate the limitations of conventional biomedical services and incorporate complementary therapies into their self-care practices. Using an interpretative phenomenological analysis (IPA) approach, in-depth interviews were conducted with reproductive-age women who reported recurrent menstrual discomfort, hormonal complaints, or emotional distress despite receiving standard medical treatment. The findings reveal four major themes: (1) unmet needs within biomedical encounters, where clinical consultations focused primarily on physical symptoms and offered limited emotional support; (2) motivations for adopting complementary therapies, driven by the desire for comfort, stress reduction, and cultural familiarity; (3) dynamic experiences in integrating medical and complementary approaches, which provided a sense of balance, agency, and improved well-being; and (4) the need for holistic, empathetic, and women-centered reproductive care. These results highlight a significant gap between women’s lived experiences and the structure of current reproductive health services, emphasizing that a strictly biomedical paradigm is insufficient to address biopsychosocial dimensions of women’s health. The study underscores the importance of developing integrative care models that combine clinical accuracy with emotional support, clear communication, and evidence-based complementary options. Such an approach is essential for enhancing the quality, safety, and responsiveness of reproductive health services in Indonesia.